2021
DOI: 10.1002/ncp.10793
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric malnutrition screening and assessment tools: Analyzing the gaps

Abstract: Pediatric healthcare professionals know that children who are malnourished have worse clinical outcomes than do their well‐nourished peers. The body of evidence in the literature on the topic of pediatric malnutrition (PMN) is growing and supports this conclusion. The goal of this article is to present the current state of practice related to PMN screening, the use of malnutrition risk screening (MNRS) tools, malnutrition assessment, and the use of malnutrition assessment tools. The purpose is also to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
3
0
1
Order By: Relevance
“…26 Fakat bu çalıĢmadaki örneklem küçüklüğü göz önüne alınarak sonuçların doğruluğu nu kanıtlamak için ileriye dönük çalıĢmalara ihtiyaç vardır. 27 Subjektif Global Nütrisyonel Değerlendirme (Subjective Global Nutritional Assessment -SGNA)…”
Section: Pediatride Malnütrisyon Değerlendirmesi Için Tarama Aracı (S...unclassified
“…26 Fakat bu çalıĢmadaki örneklem küçüklüğü göz önüne alınarak sonuçların doğruluğu nu kanıtlamak için ileriye dönük çalıĢmalara ihtiyaç vardır. 27 Subjektif Global Nütrisyonel Değerlendirme (Subjective Global Nutritional Assessment -SGNA)…”
Section: Pediatride Malnütrisyon Değerlendirmesi Için Tarama Aracı (S...unclassified
“…Presently, there is no consensus on which tool is best for identifying malnutrition or risk of malnutrition in pediatric critical illness. 40 , 41 It can be assumed that all critically ill patients with AKI who require CRRT are at risk of nutrition deterioration regardless of nutrition status on admission and benefit from a nutrition assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is based on the subjective assessment of seven parameters of a nutrition‐focused medical assessment (presence of stunting, presence of wasting, unintentional changes in weight, adequacy of dietary intake, gastrointestinal symptoms, functional capacity, and metabolic stress of disease) and three parameters of a nutrition‐focused physical examination (loss of subcutaneous fat, muscle wasting, and presence of edema). Validation studies have shown it to be related to outcome measures such as infection rates, length of stay, and readmission rates 23 . However, the SGNA is relatively complex and requires significant time and technical skills from the assessor, which may be a limitation to its use in an already overburdened healthcare system.…”
Section: Preoperative Assessment: When To Intervenementioning
confidence: 99%
“…Validation studies have shown it to be related to outcome measures such as infection rates, length of stay, and readmission rates. 23 However, the SGNA is relatively complex and requires significant time and technical skills from the assessor, which may be a limitation to its use in an already overburdened healthcare system. The SGNA scores triage patients into well nourished, moderately malnourished, or severely malnourished.…”
Section: Nutrition Assessmentmentioning
confidence: 99%